BENTUK FUNGSI, DAN MAKNA KIAS DALAM JUDUL BERITA MAJALAH GATRA DAN PEMANFAATANNYA PADA PEMBELAJARAN BAHASA INDONESIA DI PGMI STAIN PONOROGO - Puspidalia, Yuentie Sova (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2015)
Abstract: One of the uses of language to convey messageis through written language, including printed media such as newspapers or magazines. The word choices in news, both oral and written communication, are very essentialin order that the message can beconveyedwell, even they prevail beauty. With a qualitative approach, this study was aimed to uncover the types of figurative language how it functions and its utilization in Gatra magazine and on students of PGMI STAIN Ponorogo.Â  Based on the research result, it revealed figurative language in the news titles ofGatra magazine in 2013 to 2015. The figurative language used was (1) a simile used as many as 5 times, (2) metaphor 23 times, (3) metonymy 25 times, (4) anthropomorphisms 25 times, (5) Symbolic 17 times, (6) hyperbole 21 times, (7) allegory 92 times, (8) periphrasis 25 times, (9) personification 22 times, (10) Innuendo, (11) sarcasm first time, (12) synecdoche 16 times, (13) synesthesia 9 times, and (14) proverb 2 times. Thus, the total of figurative words used in the headlines inGatra magazineon 2013 to 2015 are as many as 267 times consisting of 14 types of figurative language form. If it was ranged, the use of figurative language wasdominated with the allegory type that was 86 times. Next, it is followed with metaphor and metonymy, which appeared 23 times of use respectively. The third rank was the use ofperiphrasis that was about 22 times, personification 20 times, followedwith the forth rank that was synecdoche as many as 15 times. Then, the sequential low uses of figurative language were Innuendo and sarcasm only once, proverb 4 times, simile 5 times, and synesthesia 8 times. Meanwhile, the function varied from one type of figurative language to others. The use of figurative language was revealed to function variously, i.e.,to awaken, shorten, beautify, explain, illustrate, visualize,enliven and stressed.